Do Green Practices Influence Perceived Sustainable Performance? Empirical Evidence from Hotels and Resorts in the Philippines - April Mae Ocho; Leomar Blanco Virador; Mary Rose Morales; Jonadel Ann Bahalla; Genille Grace Gumapac; Lyzel Mosqueda (International Journal of Applied Business and International Management, 2025)
Sustainability has become a critical concern in the hospitality industry due to increasing environmental issues and heightened consumer awareness. Consequently, hotels and resorts are adopting green practices to enhance their sustainability. This study aims to assess the green practices of selected hotels and resorts in Panglao, Bohol, Philippines, and evaluate their impact on perceived sustainable performance. Data were collected from 114 managers and department heads using a questionnaire and analyzed with SmartPLS version 4. The findings indicate that respondents moderately engage in energy management, water management, waste management, and green purchasing. Additionally, the data demonstrate that green practices significantly and positively affect perceived economic (c = 0.70, t = 12.53, p 0.001), environmental (c = 0.84, t = 20.41, p 0.001), social (c = 0.67, t = 11.84, p 0.001), and overall sustainable performance (c = 0.75, t = 15.73, p 0.001). Implementing green practices is thus essential for achieving sustainability. Hoteliers should integrate these practices into their strategies to enhance sustainable performance. Furthermore, effective communication and comprehensive training on green practices for employees are recommended to ensure their successful implementation.